أثر استخدام تطبيقات الجوال في تنمية دافعية تعلم الكيمياء لدى طلبة الصف الأول ثانوي في المدرسة السعودية بكوالالمبور - سالم، علي إبراهيم (Kulliyah of Education, International Islamic University Malaysia, 2020)
The current study aimed to examine the effect of using mobile applications on enhancement of motivation towards learning chemistry among first-year secondary stage among Saudi school's students in Kuala Lumpur. To achieve this objective, the researcher has designed an experiment consisting of two equivalent groups (experimental and control). Students in the experimental group were taught by using mobile applications, while students at the control group was taught the same subject using the traditional method. To investigate the improvement in students' motivation, pre-test and a post-test were performed to compare between the two groups. The results of the pre-test using independent samples t-test showed that there were no statistically significant differences between the two groups. However, the post-test by using independent samples t-test showed statistically significant differences between the two groups in favor of the experimental group. This result means that the motivation towards learning chemistry was improved among students on the experimental group. In addition, paired samples t-test was employed in order to examine any statistically significant differences before and after the experiment in each group. The results of Paired samples t-test showed a statistically significant difference between before and after in the experimental group. However, there was no statistically significant difference between before and after in the control group. Hence, the current study recommends using mobile applications while teaching chemistry in Saudi schools to improve students' motivation towards learning.